Optimizing English education curriculum for EFL students: Multimodal approach in academic writing - Yana, Dewi; Rozimela, Yenni; Hamzah, Hamzah (Journal of English Language Teaching Innovations and Materials (Jeltim), 2024)
English education faces challenges in academic writing due to technological advancements and multimodal writing. Due to the incompatibility between present curricula and student demands, the study intends to restructure the curriculum to emphasize multimodal writing projects that meet students' needs and multimodal paradigms.  The study was a type of Design and Development Research using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model, specifically the Analysis and Design stages. It involved 30 students and three team-teaching lecturers of the English Education Study Program at a private university in Indonesia. The data collection is conducted through a content analysis of the existing syllabus, needs assessment using questionnaires to the students, followed by interviews with the lecturers to further reinforce the data obtained from the questionnaires. Data analysis was conducted using a qualitative methodology that incorporates triangulation techniques and relationship mapping. The research results highlighted the need for curricula that are more tailored to multimodal projects and student needs. It implies that curriculum reconstruction has become crucial to accommodating changing needs and technologies. It is a progressive step in improving the quality of English language education.